Fortifikasi Tepung Hati Ayam Dan Tepung Kelor Dalam Pengolahan Cookies Kambambang Dan Pengarunya Terhadap Total Profil Proksimat Produk: Fortification Of Chicken Liver Flour And Moringa Flour Un The Processing Of Kambambang Cookies And Their Effects On The Total Proximate Profile Of The Product - Sonia Natasya Elul Para Lomi; Yessy Tamu Ina (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2026)
The study aimed to evaluate the effects of fortifying chicken liver flour and moringa flour on the proximate content and sensory acceptance of cassava flour-based kambambang cookies. This study used a Completely Randomized Design with four levels of fortification, namely P1 (3%), P2 (5%), P3 (7%), and P4 (9%) with five replications. The treatment was carried out by varying the levels of addition of a combination of chicken liver flour and moringa flour based on the percentage of total dry matter, while the composition of the other ingredients was kept the same in each treatment. The parameters analyzed included moisture content, pH, organoleptic tests (color, taste, texture, and overall liking), as well as total proximate profile (moisture, ash, protein, fat, and carbohydrates). The results showed moisture content ranging between 3.272-4.443% with pH 5.53-5.85. The highest panelist preference was recorded in treatment P4, mainly due to the significant improvement in taste. Fortification increases ash and protein levels, reflecting the addition of minerals and nutritional value, while the relatively high fat content (27.52-30.54%) supports the cookies' texture and flavor. Carbohydrate content ranges from 63.475-67.018% and serves as the primary energy source. The study concludes that the combination of chicken liver flour and moringa flour can simultaneously improve the proximate profile and sensory acceptance of kambambang cookies, making them a viable option for developing more nutritious and functional local foods.